Development of Salmonella Enteritidis vaccine candidate based on streptomycin independent suppressor and metabolic drift rifampicin resistance-attenuating markers. Issue 8 (August 2020) - Shehata, Awad A.; Tarabees, Reda; Elsayed, Mohamed; Wareth, Gamal; Basiouni, Shereen
Abstract: Salmonella is one of the most frequent food-borne pathogens and remains public health threat globally. The control of Salmonella in poultry, the main reservoir of non-typhoidal salmonellae, is a fundamental approach to ensure the safety of poultry products for human consumption. In the present study, a new live attenuated Salmonella enterica serovar Enteritidis vaccine candidate containing three attenuating markers based on streptomycin-independent (Sm-id) suppressor, and metabolic drift antibiotic resistance (MD- "res") was developed. The streptomycin dependent (Smd) mutants were derived from Salmonella Enteritidis wild-type strain using streptomycin. Then the Sm-id mutants were derived from the isolated Smd mutants and designated "Smd→Sm-id". A third MD- "res" marker was generated from Smd→Sm-id using rifampicin (Rif) and designated "Smd→Sm-id→Rif". The colony sizes of these mutants were stable after more than 50 serial passages on blood agar; reversion to virulence can be almost excluded. The safety and efficacy of Smd→Sm-id and Smd→Sm-id→Rif were evaluated in one-day-old commercial layer chicks. Both mutants proved to be safe in terms of clinical signs, mortalities, lesion scores of visceral organs and rapid clearance when administered orally at a dose of 10 8 colony forming unit (CFU), whereas birds inoculated with 10 8 CFU Salmonella Enteritidis wild-type strain showed diarrhea, mortalities (3/40) and necrosis in liver and spleen. Chickens vaccinated with the developed mutants showed no seroconversion; however, wild-type strain induced a significant seroconversion at 3-week-postvaccination (wpv). The developed mutants protected chickens against challenge with 10 8 CFU of Salmonella Enteritidis wild-type strain at 3-wpv. Vaccinated birds showed neither clinical signs nor mortalities during two-week post-challenge. In addition, the challenge strain could not be detected in pooled liver and spleen samples (0/5) at 7 th day post-inoculation (dpi). However, non-vaccinated challenged birds showed diarrhea and the challenge strain was re-isolated from pooled liver and spleen samples (3/5) at 7 th dpi. In conclusion, the developed mutants are safe and fully protected immunized chickens following heterologous challenge. It is obvious that the genetic characterization of these mutants and evaluation of different vaccination regimes are still in demand. Abstract : Microbiology; Infectious disease; Immunology; Salmonella ; Streptomycin-independent; Metabolic drift; Vaccine.